The Contemporary Challenges Of Unity Among Muslims - Yusuf Abdulrasaq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
More than five decades, the Muslim ummah have been facing different challenges from within and outside the Muslim world. The challenges cut across the political, socio-economic, educational, and scientific technologies. Additionally, sectarianism and the absence of tolerance among the adherence of each sect have a greater impact on the unity of the Muslim ummah. Many reasons are adducible for the high rate of disunity among ummah. These include misperception of Islamic Teachings and distortion of some of the teachings of Islam by the western world who studied Islam to destroy it. The findings revealed here that the aforementioned challenges can be tackled if the basic teachings of the Qur’an and sunnah is given high preference in all Muslim communities. Also, there is the need for a regulatory body on Islamic affairs, which will be empowered to see to Dawah activities of individual scholars. It would go a long way in preventing the spread of falsehood around the Muslim world. It is recommended that the Teachings of Islam be conveyed to the people through Scholars who are well grounded in all the components of knowledge that constitute the Islamic knowledge such as Arabic, Usul fiqh, Uluml Qur’an etc. This fundamental measure would drastically reduce the challenges facing the Muslim world. The theoretical method is adopted in this work for the proper earning of many literatures.